Assessment of Financial Inclusion: Indian Economic Growth and Micro Insurance (International Journal of Innovative Research in Engineering & Management, 2023)
The goal of this study is to look at the  recently announced plans for financial inclusion, with a  focus on how they might help groups with low incomes.  Design, methodology, and approach: This study included  microfinance and micro insurance programmes to learn  about their effects on a sample of 100 people from all walks  of life in the Agra district, India. The results show that  people have a good idea of what has been done and how  much better off they are as a result of the various financial  inclusion programmes. The populace is making use of  microfinance and micro insurance to engage in agricultural  pursuits, animal husbandry, and the establishment of their  own businesses. All types of people support the GOI's plan  to use MF and MI to revive India's sagging economy. This  study's novel findings will aid in the spread of banking  services across economically and socially disadvantaged  communities, thus fostering financial inclusion and inclusive  growth. Increased access to banking by rural residents,  spurred by lower fees, will hasten the spread of inclusive  funding and development. As this study shows, financial  institutions should work to create synergies with technology  providers in order to reach the general public and help as  many poor people as possible. This would also help them  deal with low-value, high-volume transactions in an efficient  and effective way.
Keywords: Micro Insurance; PMJDY; Financial Inclusion; PMSBY; Insurance Scheme